Effect of nano-sized Co3O4 addition on the transport properties of YBa2Cu3O7−δ - Abd Shukor, Roslan; M. H., Nazrin; I., Nor Aisyah; Lee, W. K.; Yusrianto, E.; A. N., Jannah; Shaari, Abdul Halim (AIP Publishing LLC, 2013)
The effect of nano-sized Co3O4 (10 - 30 nm) addition on YBa2Cu3O7−δ(Co3O4)x with x = 0 to 0.12 wt.% has been investigated by powder X-ray diffraction method, dc electrical resistance measurements and scanning electron microscopy. The Co3O4 particle size was larger than the coherence length but smaller than the penetration depth of the YBa2Cu3O7−δ superconductor. The onset transition temperature (T c onset) showed no significant changes for low Co3O4 addition (x ≤ 0.02 wt. %) and then decreased monotonically with the increase in Co3O4 content indicating a pair-breaking like mechanism in T c suppression for x = 0.03 to 0.12 wt. %. A sudden broadening of the superconducting-transition-width for x ≥ 0.11 wt. % was also observed. The transport properties were measured and related to the microstructure. Scanning electron micrographs showed homogeneous distribution of Co3O4 throughout the samples and the distance between particles was smaller than 1 μm but larger than the typical Abrikosov vortex lattice constant.